Comparison of solution processed As33S67 thin films deposited using primary amines of various aliphatic chain length - Jančálek, Jiří; Pálka, Karel; Kurka, Michal; Šlang, Stanislav; Vlček, Miroslav (Elsevier Science BV, 2020)
Solution processed thin chalcogenide films gain attention due to their interesting optical properties and simplicity of the deposition. The influence of the aliphatic chain length in primary amines used for As33S67 thin films deposition by spin-coating and their subsequent characterization had been studied in this paper, particularly films prepared from solutions based on n-propylamine, n-butylamine, n-pentylamine and n-hexylamine were investigated. As-prepared thin films were annealed at temperatures below glass Tg. Results gave evidence that variety in physical and chemical properties of studied amines influences required conditions of deposition process of the thin film only (such as source glass dissolution time, thin film thickness, thickness shrinkage). The structure, optical properties, surface roughness, organic residual content and chemical resistance of deposited thin films are not significantly influenced by used amine but mostly by the post-deposition annealing temperature. Thin films composition remains uninfluenced by neither used amine nor the annealing temperature.
Srovnání z roztoku deponovaných tenkých vrstev As33S67 připravených s využitím primárních aminů s různou délkou alifatického řetězce
Keywords: chalcogenide glasses; spin-coating; solution processed films; thin films; chalkogenidová skla; spin-coating; deponované vrstvy z roztoku; tenké vrstvy